1998
DOI: 10.1021/ma980211c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Polyphosphazenes:  Polymers with Pendent Tertiary Trialkylamino Groups

Abstract: Attempts have been made to synthesize polyphosphazenes with pendent tertiary amino side units via macromolecular substitution. Incorporation of -OCH2CH2N(CH3)2, -OCH2CH2OCH2-CH2N(CH3)2, and -NHCH2CH2N(CH3)2 groups was studied. Polymers in which all the side groups consisted of one type of aliphatic tertiary amino-containing unit and species that also contained 2,2,2-trifluoroethoxy or phenoxy groups as cosubstituents were examined. Related phosphazene cyclic trimers were also prepared as small molecule model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…In fact, it is interesting to note that the formation of THF oligomers has been detected in the reactions of [NPCl 2 ] n with NaOCH 2 CH 2 NMe 2 in THF. 6 However, when we carried out the preparation of the polyspirophosphazene [NP(O 2 C 12 H 8 )] n in THF as solvent, starting from [NPCl 2 ] n formed by the method described by Magill and colleagues, 2 but dissolving it in THF in the presence of K 2 CO 3 to neutralize any acid present, the products contained only traces of PTHF, never exceeding x ϭ 0.05. Therefore, it can be concluded that the PTHF in 1 comes mostly from the presence of acidic species, but that it is possible that a very small amount is due to a few unidentified cationic groups in the polydichlorophosphazene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is interesting to note that the formation of THF oligomers has been detected in the reactions of [NPCl 2 ] n with NaOCH 2 CH 2 NMe 2 in THF. 6 However, when we carried out the preparation of the polyspirophosphazene [NP(O 2 C 12 H 8 )] n in THF as solvent, starting from [NPCl 2 ] n formed by the method described by Magill and colleagues, 2 but dissolving it in THF in the presence of K 2 CO 3 to neutralize any acid present, the products contained only traces of PTHF, never exceeding x ϭ 0.05. Therefore, it can be concluded that the PTHF in 1 comes mostly from the presence of acidic species, but that it is possible that a very small amount is due to a few unidentified cationic groups in the polydichlorophosphazene.…”
Section: Resultsmentioning
confidence: 99%
“…5 In addition, it has recently been reported that THF oligomers are formed in the reactions of [NPCl 2 ] n with NaOCH 2 CH 2 NMe 2 in THF. 6 Furthermore, according to the proposed polymerization mechanism of [N 3 P 3 Cl 6 ], 7 there is a terminal -N ϭ PCl 2 ϩ group at the end of each polydichorophosphazene chain, and such groups could be capable of initiating the cationic polymerization process depicted in Scheme 2, as occurs with many other Lewis acids. 8 Therefore, the formation of diblock copolymers during the synthesis of polyphosphazenes from [NPCl 2 ] n in THF as solvent cannot be ruled out.…”
Section: Introductionmentioning
confidence: 80%
“…Poly(2-dimethylamino ethylamino)phosphazene (p(DMAEA)-ppz) was synthesized and purified as previously described (22,23). In brief, poly(dichloro)phosphazene was synthesized from hexachlorocyclotriphosphazene at 250°C in 1,2,4, trichlorobenzene using sulfamic acid and CaSO 4 2H 2 O as an initiating system (24).…”
Section: Methodsmentioning
confidence: 99%
“…147 Poly(phosphazenes) functionalized with 2-dimethylaminoethanol (DMAE) or 2-dimethylaminoethylamine (DMAEA) will exhibit slow acid-catalyzed degradation with half-lives of between 7 and 24 days. [148][149][150] Luminescent porous silicon nanoparticles (LPSiNPs) which are cleared quickly in a mouse model can be protected with dextran for prolonging the degradation time, and so they have enough time to take the therapeutic effect before being eliminated. 144 For lung disease treatment, the route of administration is another important factor for elimination time.…”
Section: Toxicity Biodegradation and Eliminationmentioning
confidence: 99%